Lady Knight - Howard, Amalie (New York : Joy Revolution, 2025)
"The daughter of a duke defies the rules of high society in regency-era London with the help of friends, including the resident rake"--
Ages 12 and up.
Grades 10-12.
Keywords: Aristocracy (Social class) -- Juvenile fiction; Secrecy -- Juvenile fiction; Aristocracy (Social class) -- Fiction; Secrecy -- Fiction; London (England) -- History -- 19th century; Juvenile fiction; Great Britain -- History -- Regency, 1811-1820; Juvenile fiction; London (England) -- History -- 19th century; Fiction; Great Britain -- History -- Regency, 1811-1820; Fiction; Historical fiction; Romance fiction; Novels